2014
DOI: 10.1177/1089253214535667
|View full text |Cite
|
Sign up to set email alerts
|

Albumin—Beyond Fluid Replacement in Cardiopulmonary Bypass Surgery

Abstract: Maintaining vascular barrier competence, preventing interstitial edema, and keeping microcirculation intact is crucial to achieve an optimal outcome in cardiopulmonary bypass surgery (CPB). Blood contact with roller pumps and foreign surfaces during CPB induces shear stress and a pressure drop across the pump boot that leads to transient systemic activation of the inflammatory and hemostatic systems. Moreover, patients after CPB often need volume resuscitation using the smallest possible amount of colloid solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…This modification of the procedure also improved microcirculatory flow in patients undergoing open heart surgery (62). It is important to note that current circuit priming strategies, especially in pediatrics, remain unsettled over the use of albumin, synthetic colloid suspensions, packed RBC units, fresh frozen plasma (FFP), or some combination therein, due to clinical concerns of hemodilution, inflammation, bleeding, and cost effectiveness (66)(67)(68)(69)(70). Though as indicated in this review, sublethal mechanical blood trauma likely plays a role in some of these complications.…”
Section: Protection Of Red Blood Cells From Mechanical Traumamentioning
confidence: 99%
“…This modification of the procedure also improved microcirculatory flow in patients undergoing open heart surgery (62). It is important to note that current circuit priming strategies, especially in pediatrics, remain unsettled over the use of albumin, synthetic colloid suspensions, packed RBC units, fresh frozen plasma (FFP), or some combination therein, due to clinical concerns of hemodilution, inflammation, bleeding, and cost effectiveness (66)(67)(68)(69)(70). Though as indicated in this review, sublethal mechanical blood trauma likely plays a role in some of these complications.…”
Section: Protection Of Red Blood Cells From Mechanical Traumamentioning
confidence: 99%
“…Albumin is widely used in clinical practice and it is known for some physiological properties other than the maintenance of oncotic pressure, such as antioxidant effects and positive effects on vessel wall integrity . Albumin interacts with the glycocalyx and reduces vascular permeability, thus enhancing microcirculatory function in critically ill patients . Albumin can restore endothelial response to acetylcholine …”
Section: Introductionmentioning
confidence: 99%
“…Albumin leakage due to alteration of the sieving efficient would be a serious consequence for cardiopulmonary bypass surgeries. Moret et al reported that lower albumin concentration induced hypotension due to lower colloid osmotic pressure (24). Testing is therefore needed to confirm that no albumin leakage occurs.…”
Section: Discussionmentioning
confidence: 99%